Rekomendasi dan Implementasi Pendidikan Kewarganegaraan di Zimbabwe: Tinjauan atas Sistem Pendidikan dan Tantangan yang Dihadapi - Maulana, Daffa Fakhri; Ramadhan, Abhi Rachma; Samsuri, Samsuri; Adnin, Ismi; Putra, Muhammad Lathief Dwi (Ideas Publishing, 2024)
Since independence, Zimbabwe has experienced a complex crisis, making it crucial for Citizenship Education (PKn) to address these challenges, yet PKn has not been implemented. This study aims to describe the political system, PKn policies, as well as the structure and curriculum content in Zimbabwe. The method used is qualitative descriptive with a literature review. Primary data is obtained from books, scientific journals, and literature related to PKn in Zimbabwe, while secondary data comes from relevant documents and previous research. Research findings indicate that the government has attempted to incorporate PKn into the education system since independence by forming the Commission of Inquiry into Education and Training, which recommended PKn to become a separate subject, but has not yet been implemented. Currently, PKn is included in other subjects such as IPS, religion, environmental science, physical education, HIV/AIDS education, history, National and Strategic Studies, and Peace, Leadership, and Conflict Transformation.